A survey of antimicrobial prescribing and dispensing practices in rural Bangladesh - Mamun, KZ; Tabassum, S; Shears, P; Hart, CA (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jan;15(1):81-4The abstract of this article is available on the PubMed website